Translation regulation via nascent polypeptide-mediated ribosome stalling. (April 2016) - Wilson, Daniel N; Arenz, Stefan; Beckmann, Roland
Highlights: Nascent polypeptides within the ribosomal tunnel can stall translation. Peptide mediated ribosome stalling is used to regulate translation. Cryo-EM structures of stalled ribosomes reveal common and distincts mechanisms. Abstract : As the nascent polypeptide chain is being synthesized, it passes through a tunnel within the large ribosomal subunit. Interaction between the nascent polypeptide chain and the ribosomal tunnel can modulate the translation rate and induce translational stalling to regulate gene expression. In this article, we highlight recent structural insights into how the nascent polypeptide chain, either alone or in cooperation with co-factors, can interact with components of the ribosomal tunnel to regulate translation via inactivating the peptidyltransferase center of the ribosome and inducing ribosome stalling.